Dyselectrolytaemia in Acute Stroke Patients, an Observational Study (Bangladesh Journal of Medicine, 2013)
Background: There are many studies on stroke, its associated conditions and their effect on stroke patients outcome, but a few studies on dyselectrolytaemia in stroke patients has been done in our country, even outside. Method: a total number of 100 randomly selected, clinically and CT proven acute stroke patients were studied at medicine units of Dhaka Medical College Hospital. Association of electrolytes imbalance among acute stroke patient were identified and correlated. Result: Out of 100 patients 29% were in between 51-60 years age group & 72% were male and 28% were female patients. Majority 53% patients had Ischaemic stroke, 45% Intracerebral haemorrhage (ICH) and only 2% had Subarachnoid haemorrhage (SAH). 53% of total acute stroke patient had dyselectrolytaemia. Among 100 acute stroke patients 62.22% of haemorrhagic stroke (p0.05) patients had dyselectrolytaemia. Total 36% of all stroke patients had serum sodium imbalance & 31% had serum potassium imbalance. In haemorrhagic stroke & ischaemic stroke patients, hyponatraemia (17% & 13%), hypernatraemia (1% & 3%), hypokalaemia (19% & 11%), hyperkalaemia (0% & 1%), hypochloraemia (9% & 6%) respectively with found. Conclusion: In haemorrhagic stroke, the incidence of dyselectrolytaemia was more than ischaemic stroke and which were mostly hyponatraemia and hypokalaemia. DOI: http://dx.doi.org/10.3329/bjmed.v22i2.13586 Bangladesh J Medicine 2011; 22: 30-34